1979
DOI: 10.1007/bf00295570
|View full text |Cite
|
Sign up to set email alerts
|

The electroencephalogram (EEG) as a research tool in human behavior genetics: Psychological examinations in healthy males with various inherited EEG variants

Abstract: The results of psychological examinations on 298 adult male probands with various inherited EEG variants are described. They may be summarized as follows: 1) The low-voltage (N) group scored high in intelligence tests, especially in spatial orientation. Personality scores revealed this group as 'normal', extravert, group-dependent, and not very energetic. 2) The borderline low-voltage (NG) group showed slight weakness in abstract thinking, short-time memory, and motor skills and a relatively strong tendency to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…For instance, LVEEG participants may exhibit decreased performance in tests of concentration along with reduced spontaneous activity (Vogel, et al, 1979). Vogel et al (1979) suggested that this pattern indicates poor modification and selective amplification of incoming stimuli as a result of weakened thalamocortical links. This was supported by research showing reduced amplitude short latency ERPs to visual and auditory stimuli (Vogel, 1986).…”
Section: Low Voltage Subtypementioning
confidence: 99%
“…For instance, LVEEG participants may exhibit decreased performance in tests of concentration along with reduced spontaneous activity (Vogel, et al, 1979). Vogel et al (1979) suggested that this pattern indicates poor modification and selective amplification of incoming stimuli as a result of weakened thalamocortical links. This was supported by research showing reduced amplitude short latency ERPs to visual and auditory stimuli (Vogel, 1986).…”
Section: Low Voltage Subtypementioning
confidence: 99%
“…Thus, elucidating the factors responsible for variations in P300, particularly those that might be heritable, has been of interest given the observed association between P300 and psychopathological conditions. Overall, there is a considerable body of evidence suggesting that brain neuroelectrical activity, whether background electroencephalograms (Vogel et al 1979;Young et al 1972;Propping et al 1980;Lykken et al 1974), averaged sensory evoked responses (Buchsbaum 1974;Rust 1975), or ERP (Steinhauer et al 1987Bock 1976;Surwillo 1980;O'Connor et al 1994;van Beijsterveldt 1996) is heritable.…”
Section: Heritability Of Alcoholism and Of P300mentioning
confidence: 99%
“…It has been suggested that in individuals with LVEEG that alpha oscillations are not absent but rather there is insufficient synchronization of local cortical alpha rhythms for the signal to be recorded on the scalp (Anokhin et al, 1992). It has also been suggested that LVEEG is a result of weakened thalamo-cortical links leading to insufficient pacemaking activity of cortical neurons (Bazanova and Vernon, 2013; Vogel et al, 1979a, 1979b). To date no studies have recorded EROs in the alpha frequency range or evaluated phase-locking or synchronization of EROs between cortical regions specifically in individuals identified with this EEG variant, as compared to those with higher amplitude variants, in order to determine if they have a relative deficiency of neuronal synchronization.…”
Section: 1 Introductionmentioning
confidence: 99%